Integrasi Nilai-Nilai Religiusitas dalam Teknik Konseling Restrukturisasi Kognitif Terhadap Penanganan Kecemasan Individu Pasca Bencana - Teuku Fadhli; M. Zainuddin; Dwi Endrasto Wibowo (INSIGHT: Jurnal Bimbingan Konseling, 2026)
Anxiety is one of the most common psychological problems experienced by individuals in post-disaster contexts and can significantly affect mental well-being and quality of life. This condition requires an intervention approach that is not only psychologically effective but also culturally and spiritually relevant. This study aims to examine the integration of Islamic religiosity values within cognitive restructuring counselling techniques as an approach to managing anxiety among post-disaster individuals. The method employed is a literature review using a descriptive-analytical approach to analyse relevant studies on cognitive restructuring and Islamic religiosity, encompassing the dimensions of Islam, Iman, and Ihsan. The integration is conducted through four main stages: identification, normalisation, distancing, and decatastrophising, which are aligned with religious values as a foundation for modifying maladaptive thought patterns. The findings indicate that the integration of Islamic religiosity values enhances the effectiveness of cognitive restructuring by providing meaning to traumatic experiences, fostering inner peace, and strengthening self-regulation. Therefore, this integrative approach offers a more holistic and contextual intervention model for addressing anxiety among post-disaster individuals, particularly within communities where religious values play a significant role in psychological life